STRATEGI PEMBERDAYAAN USAHA KECIL DAN MENENGAH - Satria, Rd. Okky (Majalah Bisnis & IPTEK, 2021)
Must be recognized as having quite a lot of effort guidance and empowerment of small businesses conducted by the agencies concerned with the development of small businesses. However, small business development efforts often overlap and do on their own. Differences in perception regarding small businesses this in turn leads to the development of small businesses are still compartmentalized boxes or oriented sectors, in which each institution builder emphasis on sectors or fields of their own proxies. The result was two things: (1) the ineffectiveness of the direction of development; (2) the lack of a uniform indicators of success, because each agency builder seeks to pursue targets and objectives in accordance with the criteria they have set themselves. Keywords: empowerment of SMEs; coaching SMEs